Unveiling Pedagogical Translanguaging: Investigating Teachers’ Translingual Practices and Purposes in ELT Classrooms - Rauteda, Khem Raj (English Language Teaching Perspectives, 2024)
Translanguaging is a linguistic practice of bi/multi-linguals where the speaker uses two or more than two languages together naturally, dynamically, and purposefully without having any conscious effort. It is used as a pedagogical resource in ELT classrooms. The study aimed to investigate and analyze the secondary-level English language teachers’ purposeful practices of translanguaging in their classroom instruction. The researcher used classroom ethnography as a research design where a purposive sampling strategy was used to collect the sample from the target population. Participant observation and the in-depth interview were used as data collection tools. The collected information was recorded, transcribed, coded, categorized, and thematically analyzed. The study found that teachers employed translanguaging as a strategy of language teaching; in the form of code mixing and translation for content simplification. It was used intentionally and purposefully to motivate, praise, and encourage the learners. Moreover, it was incorporated into the classrooms to make teaching-learning effective. The study implies that individuals’ linguistic repertoire should be used in language learning to ensure the use of the languages with which the learners are familiar. It further implies that linguistic borders should not be created by both practitioners and policymakers.